Desain Rute Pelayaran Sistem Hub and Spoke (Studi Kasus: Wilayah Papua, Indonesia) - Natalia, Christine (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2016)
Currenctly Indonesia’s government policy is focusing on designing its marine transportation and port development for logistics distribution in Indonesia to take advantage of the sea lanes. This maritime transportation concept that called sea highway is a strategy to improve connectivity and revitalize national logistic system thoroughly, in the form of organizing a scheduled big vessel regularly from western to eastern Indonesia and vice versa. One of the route is a sea highway towards Papua. This route starts from the port of Tanjung Perak that carry goods to be distributed to other ports, including the port of Manokwari (Papua). Distribution of goods in Papua region is largely use airlines and some use the sea transport. The distribution pattern by ship in Papua using